Introduction to Information Systems ( sách photocopy) - O Brien Jame A (McGraw Hill/Irwin, 2005)
Jim O’Brien’s Introduction to Information Systems 11/E has been thoroughly revised to reflect the movement toward enterprise-wide business applications. All real world case studies have been updated to correspond with this movement as well. The text’s focus is on teaching the general business manager how to use and manage the most current IT technologies like the Internet, Intranets, and Extranets for electronic commerce and enterprise collaboration, and how IT contributes to competitive advantage, reengineering business processes, and decision making. The coverage of security has been boosted in this edition to respond to increased threats of computer crime